The Relationship of managerial ownership and firm performance among selected publicly listed firms in the Philippines from 2004-2008 - Cadiz, Maria Anjeli S. (Animo Repository, 2009)
This paper is about the relationship of managerial ownership (MO) and firm performance among selected publicly listed companies in the Philippines. It covers the period from 2004-2008. MO is measured as the aggregate shares of management over the total outstanding shares of the company as disclosed in the annual reports of each company. Firm performance is measured using Tobin’s Q. Data needed for the variables MO, firm performance and the other control variables (firm size, firm age, debt ratio, advertising expense over sales, research and development over sales, fixed asset expenditure over sales, beta, specific risk) were obtained from PSE website, individual company websites, SEC library, BSP website, and the PSE monthly reports. The paper used two methods for analysis namely, the descriptive statistics analysis and the regression analysis, specifically the three-stage least squares regression analysis. For the descriptive statistics analysis, there is two panel data. Panel A is Tobin’s Q as distributed by MO while Panel B is MO as distributed by Tobin’s Q. For the regression analysis, it was employed for the high group and the low group of MO which was divided using the median value of 0.2634%. At low levels of MO (0 to 0.2634), the relationship between MO and firm performance of the publicly listed firms in the Philippines for 2004-2008 have no relationship with each other. This result is similar with the study of Chowdhury (2007), Welch (2003), Mueller and Spitz (2002) and Pedersen and Thompsen (2002). In the high group (above 0.2634 percent), firm performance influences MO. As Tobin’s Q increases, there is a corresponding decrease in MO. This is similar to the results of the study of Fahlenbrach and Stulz (2008) and Lorderer and Martin (1997). Results at the high group of managerial ownership shows that managers tend to sell their shares when the firm is performing well but managers would sell minimal shares as so as not to lose control of the firm.